KOMPOSISI JENIS TUMBUHAN HERBA PADA HUTAN PEGUNUNGAN DI SEKITAR DANAU KALIMPA’A KAWASAN TAMAN NASIONAL LORE LINDU SULAWESI TENGAH - Bakhtiar Lafare; Ramadhanil Pitopang; Samsurizal M Suleman (Biocelebes, 2018)
The research entitled “Composition of Herbs Plant Species in The Mountain Forest  Around the Kalimpa'a Lake Lore Lindu National Park Central Sulawesi” was conducted in April to June 2016. This research aims is to study and to determine the species composition of herbaceous plants that grow in the mountain forest around Kalimpa’a Lake Lore Lindu National Park area. The environmental factors such  as;  air temperature, humidity and light intensity were measured by Thermohygrometer and Lux meter.  GPS was used to measure the position geography and altitude. The data of  rainfall was obtained from the Meteorological, Climatological and Geophysics Mutiara Sis Al-Djufire Airport Palu. The research carried out in a survey with using single plot method with 50 x 50 m in size. In this  plot was subdivided into 25 subplots of 2 x 2 m² (recording units) to observe herbs diversity. The resut of the reseach showed that  there were twenty six (26) species, consist of  twenty five (25) genera and nineteen (19) families herbs plant species with the number of individuals 469. The dominant species of was Borreria alata (Aubl.) DC. with Important Value (IV) of 32,06%. It followed by  Alpinia sp and Goodyera celebica  with IV  23.73% and 21,23% respectively. Meanwhile, the lowest of Important Value (1,21%) was Genarium potentilloides. The species diversity index (H’) in this research was chategorized to medium with H’ = 2.73. Of the 26 species of herbaceous plants founded, a number of them were endemic to Sulawesi namely; Goodyera celebica Blume, Alyxia celebica D.G.Middlleton and Freycenetia minahassae Koord.